Self-Sacrifice and the Sacred: Edith Stein on Phenomenology, Christianity, and Mysticism - Jani, Anna (Religions, 2025)
In Edith Stein’s thinking, there is a gradual transition from the discovery of Christianity in her phenomenological studies to the mystical realization of her own role as a Christian. The present paper explores the historical, cultural, and personal circumstances of Stein’s approach to Christianity and reveals how philosophical insights contributed to her Christian commitment and supported her receptivity to mysticism. My thesis is that Stein’s philosophical reflection and the deepening of her personal religiosity are mutually evolving. The thesis of this paper is based on a letter written by Edith Stein to Roman Ingarden in 1927, at a time when she had not yet entered the Carmelite Order in Cologne but was already living as a monk. In this sense, the letter represents a zigzag reflection between past and present events, describing events in the apocalyptic horizon of eternity. Through recurrent reflection on the letter, I argue for the parallel development of mystical insights and philosophical achievements in Stein’s life, and finally, I show that the two are inextricably linked and contribute to a philosophical understanding of her own holocaust.